Matthew's new David at the end of exile : a socio-rhetorical study of scriptural quotations - Piotrowski, Nicholas G. (Novum Testamentum, Supplements, 2016)
Matthew crowds more Old Testament quotations and allusions into the prologue than anywhere else in his gospel. In this volume, Nicholas G. Piotrowski demonstrates the narratological and rhetorical effects of such frontloading. Particularly, seven formula-quotations constellate to establish a redemptive-historical setting inside of which the rest of the narrative operates. This setting is defined by Old Testament expectations for David's great son to end Israel's exile and rule the nations. Piotrowski contends that the rhetorical effect of this intertextual storytelling was to provide the Matthean community with an identity-in a contentious atmosphere-in terms of God's historical design for the ages, now fulfilled in Jesus and his followers.